2019
DOI: 10.1029/2019jd030868
|View full text |Cite
|
Sign up to set email alerts
|

Layer‐Wise Formation Mechanisms of an Entire‐Troposphere‐Thick Extratropical Cyclone That Induces a Record‐Breaking Catastrophic Rainstorm in Beijing

Abstract: A rarely seen entire‐troposphere‐thick (ETT) extratropical cyclone that induced a record‐breaking catastrophic rainstorm in Beijing (the largest since 1963) on 20 July 2016 was reproduced reasonably by a convection‐permitting Weather Research and Forecasting Model. This cyclone was the result of a vertical coupling of a lower, a middle, and an upper tropospheric cyclone, which formed at different times and locations. Dry air descending from the stratosphere through a tropopause folding process capped moist air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…Their results showed that the interaction of this DBV with a middle-level cyclone enhanced its intensity and precipitation. It should be noted that there is a common feature for the studies mentioned above, i.e., an LLJ was remarkable during the formation period of the DBVs [7,[17][18][19]. This feature has also been confirmed as significant by a 14-year statistic [16] and a semi-idealized simulation of DBV [20].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Their results showed that the interaction of this DBV with a middle-level cyclone enhanced its intensity and precipitation. It should be noted that there is a common feature for the studies mentioned above, i.e., an LLJ was remarkable during the formation period of the DBVs [7,[17][18][19]. This feature has also been confirmed as significant by a 14-year statistic [16] and a semi-idealized simulation of DBV [20].…”
Section: Introductionmentioning
confidence: 75%
“…For example, Dong and Zhao [17] investigated five DBVs embedded in the Meiyu front and found that a couple of upper-level westerly jet and low-level jet (LLJ) was a favorable condition for the development of these vortices. Sun et al [18] and Fu et al [19] investigated the formation mechanisms of two heavy-rainfall-producing DBVs. They found that the vorticity production (due to convergence) and the vorticity transport (due to convection) were dominant factors for the vortices' generation.…”
Section: Introductionmentioning
confidence: 99%
“…During the EEC's rapid development, its top level extended upward swiftly (from 850 hPa to 200 hPa in 21 hr). The mean VSS was about −0.84 PaÁs −1 , which was much higher than that of conventional extratropical cyclones (Fu et al, 2015;Li et al, 2019). This EEC was used to answer the two scientific questions raised above.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Fu et al (2015) analyzed an extratropical cyclone in the Yangtze River Basin and found that the top level (i.e., the uppermost level of a cyclone's vertical range) of the cyclone extended from 750 hPa to 550 hPa within 12 hr. Li et al (2019) investigated a cyclone that caused a catastrophic rainstorm in Beijing and found that it took $15 hr for the top level of this cyclone extended vertically from 500 hPa to 200 hPa. On average, the vertical stretching speed (VSS; which is calculated by the variation of a cyclone's top level divided by corresponding time) was about −0.46 PaÁs −1 for the former cyclone and around −0.56 PaÁs −1 for the latter cyclone.…”
Section: Introductionmentioning
confidence: 99%
“…A cyclone is a three-dimensional system (Kouroutzoglou et al, 2012;Jiang et al, 2020), and thus it has a vertical extent, within which each level has a remarkable closed cyclone centre belonged to the same cyclone (Li et al, 2019). The vertical extent of a cyclone is closely related to its evolution.…”
Section: Introductionmentioning
confidence: 99%